ACHIEVEMENTS AND PERSPECTIVES FOR THE CHILDHOOD NEPHROLOGY DEVELOPMENT - A.A. Baranov; T.V. Sergeeva ("Paediatrician" Publishers LLC, 2007)
Based on the analysis of the Russian and foreign literature, the authors highlighted main scientific areas of the modern nephrology. Along with the achievements in the study of the kidney diseases, there is a certain lag of the Russian nephrology as far as it concerns genetic grounds for the kidney diseases and issues of the renal impairment growth and treatment. They listed the scientific areas, whose development, in their opinion, is expedient and perspective in the foreseeable future. Key words: nephrology, children.